Do the S&P 500 index revisions affect corporate bonds and earnings performance?. Issue 10 (25th September 2018) - Chan, Keith; Zhao, Ruoyun
Abstract : Purpose: The purpose of this paper is to examine the information content in the Standard & Poor (S&P) 500 index revision and its impact on the corporate bonds and earnings of the firms whose stocks are added to or deleted from the index. Design/methodology/approach: The paper uses panel regressions on a 13-year sample of the companies added and deleted from the S&P 500 index. Findings: The regression results on the bond yields and earnings show that analysts and investors draw positive (negative) information from Index additions (deletions) and adjust their expectations of the firm performance as well as the required rates of return on corporate bonds after index revisions. Research limitations/implications: The paper suggests that deletions from the Index have significantly negative impacts on corporate bonds and earnings performance of deleted firms while additions to the index do not have significant impacts on the bonds or realized earnings of added firms. Originality/value: This paper uses corporate bonds and earnings to test competing hypotheses proposed to explain the excess stock returns of index revision, including information content hypothesis and liquidity hypothesis. The results are consistent with the information content hypothesis and do not support the liquidity hypothesis.